Characterisation of the quasi-static material behaviour of thermoplastic elastomers (TPE) under consideration of temperature and stress state. (April 2020) - Hopmann, Ch; Zimmermann, C
This article deals with the determination of the mechanical material behaviour of injection-moulded thermoplastic elastomers (TPE). For this purpose, the mechanical behaviour of TPE is investigated on basis of different materials (type and hardness) and process parameters with regard to the process-induced anisotropy. Based on these investigations, an almost isotropic material was selected for the investigations about the influence of temperature, stress state and load level. The results confirm that the hardness of the material and type of the processed material have an impact on the mechanical properties longitudinal and transversal to the flow direction. Furthermore, TPE behave quite similar to pure elastomers, as they showed a non-linear material behaviour, a stress softening after initial loading and a residual deformation after unloading. All these effects also depend on the temperature, stress state and load level, which results in a complex material behaviour. At the end of the article, two calibration approaches of a hyperelastic material model were shown (one set of parameters for all stress states vs. one set of parameters for each stress state). The second approach (one set of parameters for each stress state) shows a much higher accuracy in approximation of the test results.